Kinerja Lingkungan sebagai Moderasi pada Pengaruh Pengungkapan Lingkungan terhadap Kinerja Keuangan - Ranti Nugraheni; Zulfa Kamila (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study was conducted with the aim of examining the direct impact of environmental disclosure on financial performance. Additionally, the moderating effect of environmental performance on the relationship between these two variables was also tested. The sample data used comprised 35 selected companies listed on the Indonesia Stock Exchange (IDX) that issued sustainability reports and participated in the Corporate Performance Rating Program (PROPER) by the Ministry of Environment and Forestry (KLHK). The hypotheses in this study were tested using linear regression analysis with moderation, assisted by StataMP 16. The results indicate that financial performance, as proxied by ROA, is not affected by environmental disclosure. Furthermore, the analysis reveals that environmental performance does not moderate the effect of environmental disclosure on financial performance. Keywords: Environmental Performance, Environmental Disclosure, Financial Performance.